Rabbanite magical texts in Karaite manuscripts - Bohak, Gideon (Karaite Archives, 2013)
In spite of the recurrent polemic in Classical Karaite texts against Rabbanite dealings with magic, later Karaite manuscripts do contain some magical texts and recipes. In the present study, we examine one such manuscript (Jerusalem – The National Library of Israel Ms. Heb. 8°3652), a nineteenth-century Karaite compendium of magical and non-magical texts, copied in Troki in 1873 by Yehudah ben Shelamiel Zekharia Bezekowicz. Upon closer examination, many, and probably all, of the magical and divinatory texts and recipes found in this manuscript can be shown to be derived from the Jewish magical tradition, as transmitted in Rabbanite manuscripts. We therefore point to some of these parallels, and show that this late-Karaite manuscript incorporates textual units that go back to late antique Jewish magic, to medieval and Renaissance Jewish magic, and to more modern Jewish magic, and that its magic-related contents display no specific Karaite features. It is simply a collection of Rabbanite magical traditions copied by Karaite scribes for their own use.